The severity of hyponatremia worsens the outcome in pediatric intensive care patients - Oto, Arzu; Erdoğan, Seher; Boşnak, Mehmet (The European Research Journal, 2023)
Objectives: Hyponatremia is known to increase mortality and morbidity in adult patients. However, the significance of hyponatremia in critically ill pediatric patients is unknown, unlike in adults. We tried to determine the prevalance of hyponatremia in critically ill children and whether the severity of hyponatremia contributes to hospital stay and mortality. Methods: The results of 190 patients who met the inclusion criteria and were admitted to the pediatric intensive care unit between April 2014 and April 2017 were analyzed. Results: Eighty-six (45.3%) patients developed hyponatremia at the time of hospitalization, and Hospital‑Acquired Hyponatremia (HAH) developed in 46 (24.2%) patients during the hospitalization. Fifty-eight (30.5%) patients were normonatremic. The patients in the HAH group were significantly more septic (p = 0.015). The duration of intensive care hospitalization was significantly longer in the HAH group (p < 0.001) and significantly less in the normonatremic group (p = 0.008). Total mortality was 41% (n = 78). There was no difference between the groups regarding mortality (p = 0.4). However, the degree of hyponatremia was associated with mortality. Mortality was 24.1% in mildly hyponatremic patients, 45.6% in moderate patients, and 58.8% in severe patients (OR: 2.636, 95% CI: 1.189-5.842; OR: 4.490, 95% CI:1.439-14.008, p = 0.01). We discovered that as hyponatremia severity increased, so did the length of stay in the intensive care unit, the need for invasive ventilation, and the need for vasoactive drugs (p = 0.009, p = 0.018, and p = 0.006, respectively). Conclusions: Unlike adults, the prognostic value of hyponatremia in terms of mortality has not been determined in critically ill children. However, as the severity of hyponatremia increased, it was seen that the length of stay in the intensive care unit and mortality increased.